The Comparative Study of Notary in Indonesia & Malaysia with Two Differences Law System (Civil Law & Common Law) - Victoria, Ong Argo; Kusriyah, Sri (JURNAL AKTA, 2022)
This research aims to know the comparison of law system of notary in Indonesia and Malaysia with two differences system both are civil law and common law and also to know notary’s authorized to make authentic deeds regarding all actions, agreements and provisions required by the laws and regulations and/or that the interested party wants to be stated in the authentic deed, guarantees the certainty of the deed creation date, keeps the deed, provides grosse, copies and excerpts of the deed , all of them as long as the deeds are drawn up, they are not assigned or exempted from other officials or other people as stipulated by law. Therefore, the general power (openbaar gezaag) based on the law assigns the officer concerned to produce written evidence as desired by the parties with authentic power. The approach method used in this study is primarily a descriptive analysis approach with legal comparison methods. This means that all notaries must comply with the Notary Code of Ethics. What is stated in the notary code of ethics made by the INI organization which is the only notary organization that is legally incorporated in accordance with UUJN. The result means that all notaries must comply with the Notary Code of Ethics. While starting January 5, 2015 the Embassy in Kuala Lumpur requires appointments for all notarial services. Please bring your appointment confirmation sheet and arrive at the embassy 10 minutes before the appointment time. It can provide most of the same notarial services that a public notary is authorized by law to perform within the United States. Services are similary available as in U.S. and to foreign nationals with documents intended for use within the U.S. By following to the ACS Unit when requesting notary services: The documents to be notarized, including attachments, if any. The passport and   one   other   photo   identification.   Witnesses,   if required. (Consular staff are not alloitd to serve as witnesses.) $50.00 or the equivalent in Malaysian ringgit for each seal. Notary fees can be paid in cash or by credit card.